Color in multimedia editions - Kulishova, N.; Bilets, D. (ХНЕУ імені Семена Кузнеця, 2023)
In the era of computer technology, many multimedia editions such as websites, mobile applications, video games, etc. are being developed. Every day, millions of people use the World Wide Web to keep up with the latest news, find the information they need for work or personal matters, communicate with friends, and more.
Keywords: color; computer technology